The Existence of Community Empowerment Institutions (LPM) in the Development Plan - Widya Kurniati Mohi; Sri Lestari Gintulangi; Alwin Abdullah (Journal La Sociale, 2022)
This study aims to describe the existence of community empowerment institutions in absorbing community proposals in development plans. This study uses a qualitative method with a descriptive approach to obtain a comprehensive and in-depth understanding of the existence of community empowerment institutions in absorbing community proposals for development plans in Molokode U Village, Sipatanah District, Gorontalo City. The data collection techniques in this study used observation, interviews and documentation. The results of this study show that the existence of LPM in Molokode U Village as a Facilitator, Mediator, Motivator, Dynamist for development has been running as it should, although LPM has shown its existence in every planning activity, in practice it is still shrouded in a number of problems so that the institution in carrying out its duties is not optimal.